Progesterone increases resistance of ophthalmic and central retinal arteries in climacteric women. (April 2013) - De Souza, M. A. M.; De Souza, B. M.; Geber, S.
ABSTRACT Objective To evaluate the effect of a synthetic progestin on the vascular resistance of the ophthalmic and central retinal arteries in climacteric women, compared to placebo, using transorbital ultrasound with Doppler velocimetry. Methods We performed a prospective, randomized, double-blinded, placebo-controlled study with 216 climacteric women. Subjects were randomly allocated to one of two groups: either the group receiving placebo (one pill/day for 30 days) (n = 108) or the group receiving progestin (5 mg medroxyprogesterone acetate/day for 30 days) (n = 108). Transorbital Doppler velocimetric ultrasound was performed, before and after treatment; we measured the pulsatility index, resistance index and systole/diastole ratio. Results The mean ages of the participants in the study group and the control group were 54 ± 6.2 years (range 48–59 years) and 55 ± 6.8 years (range 46–60 years), respectively. When we compared the effect of the progestin on the central retinal artery before and after treatment, we observed a significant increase after the treatment in all Doppler indices. The same was observed when we compared the effect of the progestin on the ophthalmic artery. In the group of women receiving placebo, the Doppler indices were similar before and after treatment. Conclusions Our results demonstrate the existence of a progestogenic vasoconstrictive effect in the ophthalmic and central retinal arteries. As this study provides new data, the observed effect needs further investigations to better elucidate its extent. Moreover, our findings may be particularly useful to others interested in understanding the vascular dynamics of the cerebral vessels and to researchers running clinical trials related to hormone replacement therapy.